(untitled) (Comprehensive Journal of Science, 2026)
This study aims to design a proposed cognitive test to assess the cognitive aspects of the front crawl swimming course for third-year students at the Faculty of Physical Education and Sports Sciences in Zawiya. The researcher employed the descriptive survey method, as it is appropriate for the nature of the study. The study population consisted of 100 students attending lectures, from which a sample of 60 students was selected. The results showed that the cognitive test represents a scientific and reliable tool for evaluating students’ cognitive achievement. The research sample demonstrated a high level of knowledge regarding the questionnaire items, and most of the items exhibited acceptable psychometric values for the sample.